Breed differences in susceptibility of sheep to Haemonchus contortus - Singh, Satyaveer; Yadav, C L (The Indian Journal of Animal Sciences, 2012)
Susceptibility of Nali (group 1), 50% Nali x 50% Russian Merino/Corriedale (group 2) and 37.5% Nali x 62.5% Russian Merino/Corriedale (group 3) lambs to experimental Haemonchus contortus infection was investigated. Faecal egg output, worm counts and haematological values indicated that groups 1 and 3 lambs were more susceptible than group 2 lambs. Group 2 lambs had significantly (P